Method for producing graphite and alumina thin films - Makhanov, K. M.; Ermaganbetov, K. T.; Chirkova, L. V.; Maukebaeva, M. A. (Pleiades Publishing, 2017)
A simple comprehensible method for producing graphite and alumina films has been suggested. The optical properties of a graphite suspension in toluene and a suspension of natural clay with a high content of alumina particles in water have been studied. It has been found that the optical density of the suspensions varies from layer to layer, and the lowest optical density has been observed in upper layers. Graphite and aluminum films have been prepared by taking samples from different depths. The microstructure of the films has been examined. It has turned out that alumina particles coalesce into regularly shaped objects in the form of snowflakes. In addition, alumina films obtained from samples taken from different depths of the suspension have different thicknesses. In thin and thick films, the particle size is 0.29 and 2.81 μm or more, respectively.